The distribution of the quadratic class number - Elliott, P. D. T. A. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Д. Т. А. Эллиот. Распределение числа классов квадратичных форм P. D. T. A. Elliott. Kvadratinių formų klasių skaičiaus pasiskirstymas